A polyester having an ionic comonomer modification
Patent Information
- Application Number
- CN202510520095.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
然而,过量加入PEG可能会显著削弱材料的机械强度,导致耐用性与性能下降
Smart Images

Figure CN122978404A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to a recycled thermoplastic polyester elastomer (TPEE) with improved moisture permeability and its manufacturing method. Background Technology
[0002] Recycled thermoplastic polyester elastomer (TPEE-R) is an environmentally friendly material that combines the advantages of thermoplastics and elastomers. These materials typically consist of a hard segment and a soft segment, allowing them to be processed and reshaped when heated while retaining their elasticity and flexibility. TPEE-R is derived from recycled materials, and its ability to reduce plastic waste contributes to environmental sustainability. Thanks to its unique structural design, TPEE is widely used in a variety of products that require both mechanical durability and a soft touch.
[0003] One of the most critical challenges in the development of elastomer materials is balancing mechanical strength with ideal moisture permeability. For example, polyethylene glycol (PEG or poly(oxyethylene, POE)) is often used as a hydrophilic component to enhance moisture absorption and transport. However, excessive addition of PEG can significantly weaken the material's mechanical strength, leading to decreased durability and performance. To achieve optimal formulation design, careful selection of soft and hard segments is necessary to ensure both structural integrity and moisture permeability are maintained.
[0004] Therefore, there is an urgent need in the field for an improved TPEE-R that can enhance moisture permeability while maintaining excellent tensile properties. Summary of the Invention
[0005] To provide readers with a basic understanding, a brief summary of the invention is provided below. This summary is not a broad overview of the invention, nor is it intended to identify key / essential components of the invention or to outline its scope. Its sole purpose is to present some concepts of the invention in a simplified conceptual form as an introduction to the more detailed description that follows.
[0006] As illustrated and broadly described herein, this disclosure aims to provide an improved thermoplastic polyester elastomer that exhibits enhanced moisture permeability while maintaining excellent tensile properties. This disclosure also provides a waterproof and breathable membrane comprising the aforementioned TPEE and a method for manufacturing the TPEE.
[0007] In one embodiment, this disclosure relates to a thermoplastic polyester elastomer comprising hard segments and soft segments linked to each other by chemical bonds, wherein the hard segments comprise polyester, polyol, ionic comonomer, and the soft segments comprise polyether; the hard segments comprise about 15% to 75% by weight of the total weight of the thermoplastic polyester elastomer, and the soft segments comprise about 20% to 80% by weight of the total weight of the thermoplastic polyester elastomer; and in the hard segments, the ionic comonomer has a molar percentage (mol%) of 0.1 to 20 relative to the total molar amount of the polyester.
[0008] According to specific embodiments of this disclosure, the polyester is recycled polyester. Examples of polyesters suitable for the thermoplastic polyester elastomers of this disclosure include, but are not limited to, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polylactic acid (PLA), polycyclohexylene dimethylene terephthalate (PCT), polyethylene naphthalate (PEN), liquid crystal polyester (LCP), and combinations thereof. Preferably, the polyester used in the thermoplastic polyester elastomers of this disclosure is PET.
[0009] According to this disclosure, examples of polyols suitable for the thermoplastic polyester elastomers of this disclosure include, but are not limited to, 1,4-butanediol (BDO), ethylene glycol (EG), 1,6-hexanediol (HDO), neopentyl glycol (NPG), and combinations thereof. Preferably, the polyol suitable for the thermoplastic polyester elastomers of this disclosure is BDO.
[0010] According to this disclosure, examples of ionic comonomers suitable for the thermoplastic polyester elastomers of this disclosure include, but are not limited to, sodium dimethyl 5-sulfonate (DMSIP), sodium 4-vinylbenzenesulfonate (SSS), sodium methacrylate (SMA), potassium 3-sulfopropylmethacrylate (SPMA), sodium poly(sodium styrene sulfonate) (PSS), and combinations thereof. In one preferred embodiment of this disclosure, the ionic comonomer is DMSIP.
[0011] According to this disclosure, examples of polyethers applicable to the thermoplastic polyester elastomers of this disclosure include, but are not limited to, polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene ether glycol (PTMEG), polytetrahydrofuran (PTHF), poly(ethylene-co-propylene) glycol (PEPG), polyoxetane (POX), and combinations thereof. In a preferred embodiment of this disclosure, the polyether is PEG.
[0012] In a preferred embodiment, in the thermoplastic polyester elastomer, the hard segments are composed of recycled polyethylene terephthalate (rPET), BDO, and DMSIP; and the soft segments are composed of PEG. In another preferred embodiment, the hard and soft segments are linked together by ester bonds.
[0013] According to some embodiments of this disclosure, the hard segments account for about 45% to 55% of the total weight of the thermoplastic polyester elastomer (wt%), and the soft segments account for about 40% to 50% of the total weight of the thermoplastic polyester elastomer (wt%).
[0014] According to some embodiments of this disclosure, in the thermoplastic polyester elastomer of this disclosure, the ionic comonomer is present at a molar percentage (mol%) of 10 to 20 relative to the total molar amount of the polyester.
[0015] According to specific embodiments described herein, the thermoplastic polyester elastomer of this disclosure is characterized by having a content greater than 30,000 g / m³. 2 • Moisture vapor transmission rate (MVTR) over 24 hours.
[0016] In other embodiments, this disclosure also relates to a waterproof and breathable membrane comprising the aforementioned thermoplastic polyester elastomer (TPEE). According to some embodiments of this disclosure, the waterproof and breathable membrane has a thickness of 10 to 450 μm.
[0017] Preferably, the waterproof and breathable membrane is characterized by having a density greater than 30,000 g / m³. 2 • 24h water vapor transmission rate (MVTR).
[0018] In another embodiment, this disclosure relates to a method for producing a thermoplastic polyester elastomer (TPEE), particularly the aforementioned TPEE. The method comprises at least the following steps: (a) mixing polyester, polyol, polyether, and titanium catalyst at a first temperature and a first pressure ranging from 200°C to 250°C for 2 to 8 hours to produce an intermediate product; and (b) adding an ionic copolymer monomer and the titanium catalyst at a second temperature and a second pressure ranging from 220°C to 270°C and mixing with the intermediate product obtained in step (a) for 2 to 8 hours, thereby obtaining the thermoplastic polyester elastomer of this disclosure. According to some embodiments of this disclosure, in the method of this disclosure, the second temperature is higher than the first temperature. Furthermore, according to some embodiments of this disclosure, the ionic copolymer monomer added in step (b) is added at a molar percentage (mol%) of 0.1 to 20 relative to the total molar amount of polyester in step (a).
[0019] According to certain embodiments of this disclosure, examples of titanium catalysts applicable to step (a) of the method disclosed herein include, but are not limited to: titanium butoxide (Ti(OBu)4), titanium tetrachloride (TiCl4)), titanium isopropoxide (Ti[OCH(CH3)2]4)), titanium (IV)acetylacetonate (Ti(acac)4)), titanium dioxide (TiO2) and combinations thereof. In a preferred embodiment, the titanium catalyst is titanium butoxide.
[0020] According to the specific embodiments disclosed herein, in either step (a) or (b) of the method, the titanium catalyst is added in an amount of 0.01 to 1 mmol.
[0021] According to a partial embodiment of this disclosure, in step (a) of the method, the polyol is added in an amount equal to or greater than the weight of the polyester.
[0022] According to a partial embodiment of this disclosure, in step (a) of the method, the first pressure is about 1 atm to 2.5 atm; and in step (b) of the method, the second pressure is about less than 0.05 atm.
[0023] In some embodiments of this disclosure, the polyester suitable for the method of this disclosure is a recycled polyester. Examples of polyesters suitable for step (a) of the method of this disclosure include, but are not limited to, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polylactic acid (PLA), polycyclohexylenedimethylene terephthalate (PCT), polyethylene naphthalate (PEN), liquid crystal polyester (LCP), and combinations thereof.
[0024] According to some embodiments of this disclosure, examples of polyols applicable to the methods disclosed herein include, but are not limited to, 1,4-butanediol (BDO), ethylene glycol (EG), 1,6-hexanediol (HDO), neopentyl glycol (NPG), and combinations thereof.
[0025] According to certain embodiments of this disclosure, examples of ionic comonomers suitable for the thermoplastic polyester elastomers of this disclosure include, but are not limited to, sodium dimethyl 5-sulfonate (DMSIP), sodium 4-vinylbenzenesulfonate (SSS), sodium methacrylate (SMA), potassium 3-sulfopropyl methacrylate (SPMA), sodium poly(sodium styrene sulfonate) (PSS), and combinations thereof.
[0026] According to embodiments of this disclosure, examples of polyethers suitable for the methods disclosed herein include, but are not limited to, polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene ether glycol (PTMEG), polytetrahydrofuran (PTHF), poly(ethylene-co-propylene) glycol (PEPG), polyoxetane (POX), and combinations thereof.
[0027] In a preferred embodiment of this disclosure, the polyester is recycled polyethylene terephthalate (rPET), the polyol is BDO, the polyether is PEG, and the ionic comonomer is DMSIP.
[0028] According to optional or alternative embodiments of the present disclosure, step (b) of the method disclosed further includes combining an antioxidant with the ionic comonomer, the titanium catalyst, and the intermediate product.
[0029] With the above configuration, the thermoplastic polyester elastomer disclosed herein and the waterproof and breathable membrane containing the thermoplastic polyester elastomer prepared by the aforementioned method exhibit high moisture permeability while maintaining excellent tensile properties.
[0030] After referring to the detailed description of the embodiments and accompanying drawings below, those skilled in the art will be able to easily understand the basic spirit and other inventive objectives of the present invention, as well as the technical means and implementation methods adopted by the present invention. [Simplified Explanation of the Diagram]
[0031] To make the above and other objects, features, advantages and embodiments of the present invention more apparent and understandable, the accompanying drawings are described below:
[0032] Figure 1 This is a flowchart illustrating a method according to one embodiment of the present disclosure.
[0033] In accordance with conventional practices, the various features and components in the drawings are not drawn to scale. The drawing method is intended to best represent the specific features and components related to this invention. Furthermore, similar components / parts are referred to using the same or similar component symbols across different drawings.
Implementation Method
[0034] To make the description of this disclosure more detailed and complete, illustrative descriptions of embodiments and specific examples of the present invention are provided below; however, these are not the only forms of implementing or utilizing the specific examples of the present invention. The embodiments cover features of multiple specific examples and methods and steps for constructing and operating these specific examples, as well as their order. However, other specific examples may also be used to achieve the same or equivalent functions and order of steps.
[0035] 1. Definition
[0036] For ease of explanation, specific terms set forth herein, in the embodiments, and in the appended claims are described collectively. Unless otherwise defined herein, all technical and scientific terms herein have the same meaning as those commonly known to one of ordinary skill in the art to which this invention pertains.
[0037] Unless the context clearly indicates otherwise, the singular forms “a” and “the” used in this article include the plural forms.
[0038] The descriptions of numerical ranges in this document are for ease of expression only and are intended to cover each specific value within that range. Unless otherwise stated, each individual value within the numerical range is considered to be explicitly disclosed and incorporated into this specification.
[0039] The term "about" as used herein means, with respect to a particular numerical value, falling within the acceptable range of error as recognized by one of ordinary skill in the art; this range depends in part on the method of measurement or determination of the value, i.e., the limitations of the measurement system. Unless otherwise expressly stated in specific embodiments or other parts of this specification with respect to a particular test, result, or implementation, the term "about" means, in accordance with the practice of the art, falling within one standard deviation, or within a range of at most 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.
[0040] As used herein, the terms "comprising," "having," "containing," or any variations thereof, mean non-exclusive inclusion, subject only to any expressly stated limitations. For example, a composition, mixture, process, or method that comprises several elements is not necessarily limited to those elements, but may also include those not expressly listed, or other elements inherent to the composition, mixture, process, or method.
[0041] As used in this specification, phrases such as "in one embodiment," "in some embodiments," and similar expressions generally indicate that a particular feature, structure, or property described thereafter may be included in at least one embodiment of this disclosure, and possibly in multiple embodiments (however, it should be noted that such statements do not necessarily refer to the same embodiment). The examples or exemplary language provided in this specification (e.g., "suchas") are for illustrative purposes only and do not constitute a limitation on the scope of its claims. Nothing in this specification should be construed as indicating that any element not claimed in the claims is necessary to implement this disclosure.
[0042] Unless otherwise expressly stated or clearly contradicted by the context, all methods described in this specification may be performed in any appropriate order.
[0043] As used in this article, "ionic comonomer" refers to a monomer containing one or more ionic functional groups, such as sulfonates (-SO3). - ), carboxylates (-COO) - ), phosphate (-PO4) 3- ) or ammonium salt (-NR4) + Monomers containing groups such as ions can participate in polymerization reactions to form ionic polymers (such as ionic polymers, polyelectrolytes, or ionic copolymers). These monomers introduce ionic forces into the polymer structure, thereby affecting its properties such as hydrophilicity, electrical conductivity, mechanical strength, and thermal stability.
[0044] The term "moisture vapor transmission rate" or its abbreviation "MVTR" used in this article refers to the amount of water vapor that passes through a material within a specific time period, usually expressed in grams per square meter per day (g / m²). 2 / day) or grams per square meter per 24 hours (g / m²) 2 The value is expressed as / 24h. It indicates the air permeability of the water vapor barrier material; the higher the value, the greater the moisture permeability.
[0045] The weight percentage (wt%) referred to herein means the percentage of the mass / weight of a specific component to the total mass of the overall thermoplastic polyester elastomer. Unless otherwise expressly stated, all percentages mentioned herein are calculated as a weight percentage based on the total weight of the thermoplastic polyester elastomer. According to certain specific embodiments, the content of hard segments in the thermoplastic polyester elastomer is 15% to 75% (e.g., 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, or 75 wt%) of the total weight of the thermoplastic polyester elastomer; while the content of soft segments is 20% to 80% (e.g., 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80 wt%).
[0046] The molar percentage (mol%) referred to herein is the ratio of the number of moles of one component (e.g., component A) to the number of moles of another specified component (e.g., component B), expressed as a percentage, with component B serving as the comparison benchmark. In the specific embodiments disclosed herein, when preparing thermoplastic polyester elastomers, the amount of ionic comonomer added is based on the total number of moles of polyester used, and its addition is expressed as a molar percentage. In other words, the percentage of the number of moles of the ionic comonomer to the number of moles of polyester is its mol%. Specifically, the amount of ionic comonomer added can be from 0.1% to 20.0% of the polyester molar number, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, and 20.0 mol%. Detailed Implementation
[0047] This disclosure is based, at least in part, on the discovery that adding ionic copolymer monomers and polyols in a specific ratio during the preparation of thermoplastic polyester elastomers (TPEE) can improve the moisture permeability of the TPEE while maintaining its physical properties. Accordingly, this disclosure provides a novel TPEE with improved properties and high moisture permeability, as well as a waterproof and breathable membrane comprising this TPEE and a method for its preparation.
[0048] 2.1 Thermoplastic polyester elastomer (TPEE) and its manufacturing method
[0049] The first embodiment of this disclosure relates to a thermoplastic polyester elastomer and a method for manufacturing the same. Please refer to the drawings. Figure 1 .
[0050] Figure 1 This is a flowchart illustrating a method 1010 according to an embodiment of this disclosure. The method 10 includes at least the following steps, wherein... Figure 1 The symbols S101 to S102 represent the following respectively: S101: A polyester, a polyol, a polyether, and a titanium catalyst are mixed at a first temperature in the range of 200°C to 250°C and a first pressure for 2 to 8 hours to obtain an intermediate product; and S102: At a second temperature and a second pressure ranging from 220°C to 270°C, an ionic copolymer monomer and the titanium catalyst are added and mixed with the intermediate product obtained from step S101 for 2 to 8 hours to obtain the thermoplastic polyester elastomer disclosed herein.
[0051] This manufacturing method begins with an esterification reaction, which is carried out by mixing a polyester, a polyol, a polyether, and a titanium catalyst in a first reactor at a first temperature and a first pressure, and continuing the reaction for 2 to 8 hours to carry out an esterification reaction promoted by the titanium catalyst (step S101).
[0052] According to some embodiments of this disclosure, the titanium catalyst can be an alkoxide-based, halide-based, acetylacetone-based, or heterogeneous titanium catalyst. Non-limiting titanium catalysts suitable for the methods of this disclosure include titanium butoxide (Ti(OBu)4), titanium tetrachloride (TiCl4), titanium isopropoxide (Ti[OCH(CH3)2]4), titanium (IV)acetylacetonate (Ti(acac)4), titanium dioxide (TiO2), and combinations thereof. In a preferred embodiment, the titanium catalyst is titanium butoxide. The amount of titanium catalyst added can be adjusted according to actual needs. According to some embodiments of this disclosure, the titanium catalyst is added in an amount ranging from 0.01 to 1 mmol, preferably in an amount of about 0.1 to 0.3 mmol.
[0053] Alternatively or unnecessarily, the titanium catalyst can be prepared by coordinating a polyol with titanium atoms to form a polyol-coordinated titanium catalyst (coordination-modified titanium catalyst), which is then used to esterify a polyester and react with the polyol to produce a thermoplastic polyester elastomer. The polyol used for coordination with titanium is different from the polyol used in step S101. Typically, the titanium catalyst used in this method can be prepared by reacting a titanium compound with a polyol in a molar ratio of about 1:1 to 1:3, such as 1:1, 1:2, or 1:3. Non-limiting examples of titanium compounds include tetramethoxytitanium (TMT), tetraethoxytitanium (TET), tetraisopropoxytitanium (TPT), or tetrabutoxytitanium (TBT). Non-limiting examples of suitable polyols for coordination include xylitol, sorbitol, maltol, erythritol, or mannitol. Optionally, the catalyst may further react with titanium atoms and an alkaline substance in a molar ratio of about 1:1 to 100:1 to enhance its stability in water. Non-limiting examples of alkaline compounds include amine compounds or alkali metal compounds, such as lithium hydroxide, sodium hydroxide, ammonium hydroxide, tetrabutylammonium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, lithium acetate, sodium acetate, potassium acetate, or triethylamine.
[0054] In step S101, the amounts of polyester, polyol, and polyether can be adjusted according to actual needs, for example, based on the weight ratio of hard segments to soft segments. According to embodiments disclosed herein, the mass ratio of polyester to polyether can be approximately 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, or 5:1. As for the polyol, its addition amount is equal to or greater than the weight of the polyester. According to some embodiments disclosed herein, the addition amount of the polyol is greater than the weight of the polyester.
[0055] According to specific embodiments of this disclosure, the polyester is recycled polyester. Specific examples of polyesters suitable for the thermoplastic polyester elastomers of this disclosure include, but are not limited to, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polylactic acid (PLA), polycyclohexylene dimethylene terephthalate (PCT), polyethylene naphthalate (PEN), and liquid crystal polyester (LCP).
[0056] Examples of polyethers applicable to thermoplastic polyester elastomers disclosed herein include, but are not limited to, polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene ether glycol (PTMEG), polytetrahydrofuran (PTHF), poly(ethylene-co-propylene) glycol (PEPG), and polyoxetane (POX).
[0057] Examples of polyols applicable to the thermoplastic polyester elastomers disclosed herein include, but are not limited to, 1,4-butanediol (BDO), ethylene glycol (EG), 1,6-hexanediol (HDO), and neopentyl glycol (NPG).
[0058] According to some embodiments of this disclosure, the reaction in step S101 is carried out in a first reactor at a first temperature, wherein the temperature range is 200°C to 250°C, preferably 220°C. Furthermore, the first pressure in the first reactor is approximately 1 atm to 2.5 atm, for example, 1, 1.5, 2, and 2.5 atm. According to some specific embodiments, the reaction in step S101 is carried out at 1 atm for 6 hours to form an intermediate product.
[0059] The intermediate product is transferred to a second reactor for polymerization (step S102). In this step, an ionic comonomer is added again to the second reactor along with the titanium catalyst to react with the intermediate product. The reaction is carried out at a second temperature, ranging from 220°C to 270°C, and at a second pressure below 0.05 atm, for a reaction time of 2 to 8 hours, preferably 3 to 4 hours. The second temperature can be adjusted as needed, but must be higher than the first temperature. According to one embodiment, the second temperature is 245°C, and the second pressure is reduced to below 1 Torr (0.0013 atm).
[0060] According to some embodiments of this disclosure, in step S102 of this method, the addition of the ionic comonomer is calculated based on its molar percentage (mol%) relative to the total molar content of the polyester. Specifically, the molar percentage of the ionic comonomer ranges from 0.1 mol% to 20 mol%, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, or 20.0 mol%. In a preferred embodiment of this disclosure, the molar percentage of the ionic comonomer ranges from 10 mol% to 20 mol%. Examples of ionic comonomers applicable to the thermoplastic polyester elastomers disclosed herein include sodium dimethyl 5-sulfonate (DMSIP), sodium 4-vinylbenzenesulfonate (SSS), sodium methacrylate (SMA), potassium 3-sulfopropylmethacrylate (SPMA), poly(sodium styrene sulfonate) (PSS), and combinations thereof; however, they are not limited thereto.
[0061] According to a partial embodiment of this disclosure, in step S102, the titanium catalyst is added again in an amount ranging from 0.01 to 1 mmol, preferably in an amount of about 0.1 to 0.3 mmol.
[0062] Alternatively or additionally, an antioxidant may be added to the second reactor and mixed with the aforementioned ionic comonomer, titanium catalyst, and intermediate product. Those skilled in the art can select an appropriate antioxidant based on their knowledge. In one specific embodiment, the antioxidant is a butylated hydroxytoluene derivative.
[0063] According to a partial embodiment of this disclosure, the polyester in step S101 is recycled polyethylene terephthalate (rPET), the polyol in step S101 is 1,4-butanediol (BDO), the polyether in step S101 is polyethylene glycol (PEG), and the ionic comonomer in step S102 is sodium dimethyl isophthalate-5-sulfonate (DMSIP). After completing steps S101 and S102 under the aforementioned conditions, a thermoplastic polyester elastomer comprising hard segments and soft segments is produced.
[0064] The thermoplastic polyester elastomer prepared by the above method will be further described below. According to some embodiments of this disclosure, the hard and soft segments are connected to each other by chemical bonds. In a specific embodiment of this disclosure, the hard segments of the thermoplastic polyester elastomer prepared by the aforementioned method are composed of the polyester, polyol, and ionic copolymer monomers (specifically, repolymerized polyethylene terephthalate (rPET), BDO, and DMSIP, respectively); while the soft segments are composed of polyethers (specifically, PEG). Therefore, in this specific embodiment, the hard and soft segments are bonded to each other via ester bonds.
[0065] The weight ratio (or weight percentage) of hard segments to soft segments in the resulting TPEE depends on the amount of starting material used in the preparation process. According to some embodiments of this disclosure, the hard segments account for approximately 15% to 75% (wt%) of the total weight of the TPEE, for example, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, and 75%. The soft segments account for approximately 20% to 80% (wt%) of the total weight of the TPEE, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, and 80%. In some preferred embodiments, the hard chain segment accounts for approximately 45% to 55% (wt%) of the total weight of the TPEE, for example, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54 and 55%; while the soft chain segment accounts for approximately 40% to 50% (wt%) of the total weight of the TPEE, for example, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 and 50%.
[0066] Similarly, the proportion of ionic comonomers in the final TPEE product also depends on the amount of starting material used in the preparation process. According to some embodiments of this disclosure, the molar percentage (mol%) of the ionic comonomers relative to the total molar content of the polyester (e.g., rPET as described in this disclosure) is 0.1% to 20%. For example, the molar percentage of the ionic comonomer (e.g., DMSIP) can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, and 20.0%. In a preferred embodiment, the molar percentage of the ionic comonomer relative to the total molar content of the polyester is 10 to 20 mol%.
[0067] According to some embodiments of this disclosure, after qualitative identification, the TPEE of this disclosure has the following characteristics: tensile strength of 100 to 500 kgf / cm². 2 The rubber has a hardness of 20 to 60D and a melting point of 150 to 210℃.
[0068] With the above configuration, the method disclosed herein (including steps S101 to S102) enables the TPEE to exhibit the desired physical properties by adding a specific amount of ionic comonomer and defining a specific ratio of ionic comonomer to polyester.
[0069] 2.2 Waterproof and breathable membrane containing the aforementioned TPEE
[0070] This disclosure also aims to provide a waterproof and breathable membrane comprising TPEE according to some embodiments of this disclosure. Compared to conventional membrane materials, this waterproof and breathable membrane exhibits superior moisture permeability.
[0071] Specifically, the waterproof and breathable membrane can be made directly from TPEE or prepared from a combination of TPEE and other polymers. TPEE material can be made into a non-porous waterproof and breathable membrane using techniques and methods known to those skilled in the art. For example, the waterproof and breathable membrane can be produced from TPEE through co-extrusion processes, solvent coating, hot lamination, and / or meltblown extrusion, depending on actual needs. In some embodiments of this disclosure, the waterproof and breathable membrane is produced by co-extrusion using a T-die extruder.
[0072] The thickness of the waterproof and breathable membrane can be adjusted according to actual needs. For example, in this disclosure, the thickness of the waterproof and breathable membrane can be adjusted to a range of 10 to 450 μm by adjusting equipment (e.g., a T-die machine). Preferably, the thickness of the waterproof and breathable membrane is about 20 μm.
[0073] According to some embodiments of this disclosure, the waterproof and breathable membrane prepared from the aforementioned TPEE exhibits excellent moisture permeability. According to specific embodiments of this disclosure, after standard testing using a fabric moisture permeability tester, its water vapor transmission rate (MVTR) is greater than 30,000 g / m². 2 • 24h. Preferably, the MVTR of the waterproof and breathable membrane ranges from approximately 50,000 to 100,000 g / m². 2 ·24h.
[0074] With the above configuration, the waterproof and breathable membrane containing the TPEE disclosed herein exhibits excellent moisture permeability.
[0075] Example
[0076] Materials and Methods
[0077] Chemicals list
[0078] The chemicals and starting materials used in this embodiment are listed in Table 1 below. Table 1: List of Chemicals
[0079] General preparation process of thermoplastic polyester elastomers
[0080] Recycled PET (r-PET), 1,4-butanediol, polyethylene glycol (PEG, molecular weight 2000 g / mol), and tetrabutyl titanate were added to the transesterification / transesterification reactor. The reaction was carried out at 220°C and atmospheric pressure for 6 hours.
[0081] After the transesterification reaction is complete, the reaction products are transferred to the polymerization reactor. Then, ionic comonomers (e.g., DMSIP), sodium acetate, and antioxidants (e.g., ...) are added. 1010) with tetrabutyl titanate. The temperature is raised to 245°C while the pressure is reduced to below 1 Torr, and the reaction continues for 3 to 4 hours.
[0082] Once the specified mechanical torque value is reached, the polymerization reactor is depressurized to atmospheric pressure. Next, the ester strip is cooled in a water bath and then granulated using a granulator, completing the preparation of recycled thermoplastic polyester elastomer resin (i.e., TPEE as described in this disclosure).
[0083] Testing and identification of physical properties
[0084] Tensile strength (ASTM D638)
[0085] Tensile strength is measured using a universal testing machine. The material is fabricated into dumbbell-shaped test pieces and equipped with a two-point elongation meter to accurately measure displacement and stress. Tensile breaking strength is defined as the maximum stress that a material can withstand before failure.
[0086] Melting point (ISO 11357-1)
[0087] Melting point is determined using a differential scanning calorimeter (DSC). A small amount of sample is sealed in a sample pan and placed inside the DSC instrument. The sample is heated at a fixed rate of 10°C per minute. The DSC records the heat flow change and observes an endothermic peak near the melting point. The temperature corresponding to the maximum value of this endothermic peak is defined as the melting point of the sample.
[0088] Hardness (ASTM D2240)
[0089] Hardness testing was performed using a Shore D hardness tester. A 6mm thick specimen was prepared, and a 50N load was applied vertically to the surface of the specimen. The hardness value was recorded after 1 second of pressure. Multiple measurements were taken at different locations on the specimen, and the average value was taken as the final hardness data.
[0090] Moisture permeability (JIS L1099B-1)
[0091] Moisture permeability was measured using a water vapor permeability meter. In this procedure, a test cup containing potassium acetate as a desiccant was sealed with an expanded polytetrafluoroethylene (ePTFE) membrane. The test sample was placed with the functional side facing the test cup, which was then inverted and immersed in water. After a predetermined time, the change in the weight of the test cup was measured to calculate the amount of water vapor permeating the sample. The final result was the weight of water vapor permeating per square meter per 24 hours (g / m²). 2 •24h) indicates its water vapor transmission rate.
[0092] Example 1: Preparation of the thermoplastic polyester elastomer (TPEE) disclosed herein
[0093] To evaluate whether the TPEE prepared according to the method disclosed herein possesses the desired physical properties and moisture permeability, three different TPEE samples (Examples 1.1 to 1.3) were synthesized with different raw material compositions according to the steps described in the "Materials and Methods" section and Section 2.1 above. In addition, control samples of TPEE (Comparative Examples 1.1 to 1.3) were prepared according to a similar procedure, the difference being the addition of an ionic copolymer monomer (e.g., DMSIP) to the TPEE control samples. Specific experimental procedures are described below:
[0094] Example 1.1
[0095] 25 kg of recycled PET, 25 kg of 1,4-butanediol, 13.5 kg of PEG, and 45 g of tetrabutyl titanate were added to an esterification / transesterification reactor. The reaction was carried out at 220 °C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, where 2 kg of DMSIP and 45 g of sodium acetate were added. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE as described in this disclosure (Example 1.1).
[0096] Example 1.2
[0097] 20 kg of recycled PET, 21 kg of 1,4-butanediol, 18 kg of PEG, and 45 g of tetrabutyl titanate were added to an esterification / transesterification reactor. The reaction was carried out at 220 °C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, where 3.5 kg of DMSIP and 45 g of sodium acetate were added. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE as described in this disclosure (Example 1.2).
[0098] Example 1.3
[0099] 15 kg of recycled PET, 17 kg of 1,4-butanediol, 22.5 kg of PEG, and 45 g of tetrabutyl titanate were added to an esterification / transesterification reactor. The reaction was carried out at 220 °C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, where 4.25 kg of DMSIP and 45 g of sodium acetate were added. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE as described in this disclosure (Example 1.3).
[0100] Comparative Example 1.1
[0101] Recycled PET (19.5 kg), 1,4-butanediol (18 kg), PEG (18 kg), and tetrabutyl titanate (45 g) were added to an esterification / transesterification reactor. The reaction was carried out at 220°C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, and additives were added to the polymerization reactor. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE (Comparative Example 1.1).
[0102] Comparative Example 1.2
[0103] Recycled PET (16-15 kg), 1,4-butanediol (15 kg), PEG (22.5 kg), and tetrabutyl titanate (45 g) were added to an esterification / transesterification reactor. The reaction was carried out at 220°C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, and additives were added to the polymerization reactor. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE (Comparative Example 1.2).
[0104] Comparative Example 1.3
[0105] 13 kg of recycled PET, 12 kg of 1,4-butanediol, 27 kg of PEG, and 45 g of tetrabutyl titanate were added to an esterification / transesterification reactor. The reaction was carried out at 220 °C and atmospheric pressure for 6 hours. After the esterification reaction was completed, the product was transferred to a polymerization reactor, and additives were added to the polymerization reactor. 1010 (90g) and tetrabutyl titanate (34g). The temperature was raised to 245°C while the pressure was simultaneously reduced to below 1 Torr, and the reaction continued for 3 to 4 hours. When the specified mechanical torque value was reached, the polymerization reactor was depressurized to atmospheric pressure. Then, the ester strip was cooled in a water bath and cut into granules using a granulator, thereby completing the preparation of TPEE (Comparative Example 1.3).
[0106] Example 2: Identification of the thermoplastic polyester elastomer (TPEE) disclosed herein
[0107] The purpose of this experiment is to compare the physical properties and moisture permeability of the embodiments disclosed herein with those of the control group. To achieve this purpose, the TPEE samples prepared in Examples 1.1 to 1.3 and Comparative Examples 1.1 to 1.3 were subjected to melting point and hardness tests according to the procedures described in the "Materials and Methods" section. Furthermore, a portion of the TPEE was heated and melted, and then injection molded into dumbbell-shaped test pieces (25 mm long, 6 mm wide, and 3 mm thick), which were then subjected to tensile strength tests according to the same procedure. Further, after the TPEE was heated and melted, it was extruded into a film using T-DIE, then cooled and wound to form a non-porous waterproof and breathable membrane with a thickness of 20 ± 10 μm. The moisture permeability of the resulting membrane material was also evaluated according to the procedures described in the "Materials and Methods" section.
[0108] The physical properties of TPEE and the moisture permeability of the resulting films are shown in Table 2. Table 2: Comparison Results
[0109] As shown in Table 2, the experimental results demonstrate that, compared to TPEE without added ionic comonomer, the TPEE prepared with added ionic comonomer exhibits both excellent tensile strength and high water vapor transmission rate (MVTR). Specifically, Example 1.1, containing 5 mol% ionic comonomer, achieves a tensile strength of 451 kgf / cm². 2 MVTR is 35,442 g / m 2 • Days; while Comparative Example 1.1, which does not contain ionic comonomers, has a tensile strength of only 391 kgf / cm. 2 MVTR is 30,227 g / m 2 ·sky.
[0110] Furthermore, a comparison of Example 1.2 and Comparative Example 1.1, both containing the same PEG content (40 wt%), showed that their tensile strengths were comparable (346 kgf / cm², respectively). 2 With 391 kgf / cm 2 However, the MVTR of Example 1.2, which contains an ionic comonomer, is 55,131 g / m³. 2 • Days, for Comparative Example 1.1, MVTR (30, 227 g / m²) 2 The water vapor permeability of TPEE is 1.8 times that of 1 day. This result shows that the addition of ionic comonomers can significantly improve the water vapor permeability of TPEE without sacrificing its mechanical strength.
[0111] On the other hand, the hardness values of the experimental and control groups remained relatively stable. For example, Example 1.1 and Comparative Example 1.1 showed similar hardness values of 55D and 53D, respectively, while Example 1.3 and Comparative Example 1.3 showed values of 28D and 30D, respectively. These results indicate that, within the scope of this study, the addition of ionic copolymer monomers had no significant effect on the hardness of TPEE.
[0112] Similarly, the melting point was not significantly affected by the presence of ionic comonomers. The melting points of the experimental and control samples were similar across all samples, indicating that this modification did not substantially alter the thermal stability of TPEE.
[0113] Overall, these results show that adding an appropriate amount of ionic comonomer to TPEE can achieve a balance between effectively improving tensile strength and moisture permeability, while maintaining similar hardness and thermal properties.
[0114] It should be understood that the above descriptions of the various embodiments are merely illustrative, and those skilled in the art can make various modifications. The foregoing specification, embodiments, and data provide a complete description of the structure and use of exemplary embodiments of the present invention. Although various embodiments of the present invention have been described above in some detail or with reference to one or more individual embodiments, those skilled in the art can make various changes to the disclosed embodiments without departing from the spirit and scope of the present invention. [Symbol Explanation]
[0115] 10 methods Steps S101-S102
Claims
1. A thermoplastic polyester elastomer comprising a hard segment and a soft segment linked together by chemical bonds, wherein, The hard segment comprises a polyester, a polyol, and an ionic comonomer, and the soft segment comprises a polyether; The hard chain segment accounts for approximately 15% to 75% of the total weight of the thermoplastic polyester elastomer, and the soft chain segment accounts for approximately 20% to 80% of the total weight of the thermoplastic polyester elastomer; and In this hard segment, the ionic comonomer has a molar percentage of 0.1 to 20 relative to the total molar amount of the polyester.
2. The thermoplastic polyester elastomer as claimed in claim 1, wherein the polyester is a recycled polyester.
3. The thermoplastic polyester elastomer as claimed in claim 1, wherein the polyester is selected from the group consisting of polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polylactic acid, dimethyl cyclohexane terephthalate, polyethylene naphthalate, liquid crystal polyester, and combinations thereof.
4. The thermoplastic polyester elastomer as claimed in claim 1, wherein the polyol is selected from the group consisting of 1,4-butanediol, ethylene glycol, 1,6-hexanediol, neopentyl glycol, and combinations thereof.
5. The thermoplastic polyester elastomer of claim 1, wherein the ionic comonomer is selected from the group consisting of sodium dimethyl isophthalate-5-sulfonate, sodium 4-vinylbenzenesulfonate, sodium methacrylate, potassium propyl 3-sulfonate methacrylate, sodium polystyrene sulfonate, and combinations thereof.
6. The thermoplastic polyester elastomer as claimed in claim 1, wherein the polyether is selected from the group consisting of polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, polytetrahydrofuran, poly(ethylene-co-propylene) alcohol, polyoxybutane, and combinations thereof.
7. The thermoplastic polyester elastomer of claim 1, wherein the polyester is a recycled polyethylene terephthalate, the polymethyl terephthalate is 1,4-butanediol, the ionic comonomer is sodium dimethyl isophthalate-5-sulfonate, and the polyether is polyethylene glycol.
8. The thermoplastic polyester elastomer as described in claim 1, wherein the chemical bond is an ester bond.
9. The thermoplastic polyester elastomer as claimed in claim 1, wherein the hard segment accounts for 45% to 55% of the total weight of the thermoplastic polyester elastomer, and the soft segment accounts for 40% to 50% of the total weight of the thermoplastic polyester elastomer.
10. The thermoplastic polyester elastomer of claim 1, wherein the ionic comonomer has a molar percentage of 10 to 20 relative to the total molar amount of the polyester.
11. The thermoplastic polyester elastomer as described in claim 1, characterized in that... It has a strength greater than 30,000 g / m 2 • 24h water vapor transmission rate.
12. A waterproof and breathable membrane comprising the thermoplastic polyester elastomer as described in claim 1, wherein the waterproof and breathable membrane has a thickness of 10 to 450 μm.
13. The waterproof and breathable membrane as claimed in claim 12, wherein the waterproof and breathable membrane is characterized by having a water vapor permeability of greater than 30,000 g / m²·24h.
14. A method for preparing the thermoplastic polyester elastomer as described in claim 1, comprising: (a) A polyester, a polyol, a polyether, and a titanium catalyst are mixed at a first temperature and a first pressure in the range of 200°C to 250°C for 2 to 8 hours to produce an intermediate product; and (b) At a second temperature and a second pressure ranging from 220°C to 270°C, an ionic copolymer monomer and the titanium catalyst are added and mixed with the intermediate product obtained from step (a) for 2 to 8 hours to obtain the thermoplastic polyester elastomer. The second temperature is greater than the first temperature. The ionic comonomer added in step (b) has a molar percentage of 0.1 to 20 relative to the total molar amount of the polyester in step (a).
15. The method of claim 14, wherein in step (a), the titanium catalyst is selected from the group consisting of tetrabutyl titanate, titanium tetrachloride, isopropyl titanate, titanium acetylacetonate, titanium dioxide, and combinations thereof.
16. The method of claim 15, wherein the titanium catalyst is tetrabutyl titanate.
17. The method of claim 14, wherein in step (a) or (b), the titanium catalyst is added in an amount of 0.01 to 1 mmol.
18. The method of claim 14, wherein in step (a), the polyol is added in an amount equal to or greater than the weight of the polyester.
19. The method of claim 14, wherein in step (a), the first pressure is 1 atm to 2.5 atm, and in step (b), the second pressure is less than 0.05 atm.
20. The method of claim 14, wherein the polyester is a recycled polyester selected from the group consisting of polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polylactic acid, dimethyl cyclohexane terephthalate, polyethylene naphthalate, liquid crystal polyester, and combinations thereof.
21. The method of claim 14, wherein the polyol is selected from the group consisting of 1,4-butanediol, ethylene glycol, 1,6-hexanediol, neopentyl glycol, and combinations thereof.
22. The method of claim 14, wherein the polyether is selected from the group consisting of polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, polytetrahydrofuran, poly(ethylene-co-propylene) alcohol, polyoxybutane, and combinations thereof.
23. The thermoplastic polyester elastomer of claim 1, wherein the ionic comonomer is selected from the group consisting of sodium dimethyl isophthalate-5-sulfonate, sodium 4-vinylbenzenesulfonate, sodium methacrylate, potassium propyl 3-sulfonate methacrylate, sodium polystyrene sulfonate, and combinations thereof.
24. The method of claim 14, wherein the polyester is a recycled polyethylene terephthalate, the polyol is 1,4-butanediol, the ionic comonomer is sodium dimethyl isophthalate-5-sulfonate, and the polyether is polyethylene glycol.
25. The method of claim 14, wherein in step (b), the method further comprises mixing an antioxidant with the ionic comonomer, the titanium catalyst, and the intermediate product.